Strategy of Islamic Service Quality and Spiritual Care Services in Enhancing Patient Loyalty Through Holistic Satisfaction (Case Study: Inpatients at Jabal Rahmah Hospital) - Dani Dani; Wahyu Aldino; Ari Yopi Ispa (DINASTI RESEARCH, 2026)
This study examines the influence of Islamic service quality and spiritual care services on patient loyalty, with holistic (kaffah) satisfaction as a mediating variable. The study is motivated by gap phenomena and contemporary business challenges, particularly the decline in the number of inpatients at Jabal Rahmah General Hospital amid increasingly intense competition in the healthcare service industry. In the context of Islamic hospitals, patient satisfaction alone is insufficient; hospitals are required to foster long-term patient loyalty through comprehensive and value-based services. The population of this study consisted of inpatients at Jabal Rahmah General Hospital in 2025. A total of 100 respondents were selected using simple random sampling. Data were collected through questionnaires and analyzed using multiple linear regression, t-tests, coefficient of determination (Adjusted R²), and path analysis. The findings indicate that Islamic service quality and spiritual care services have a positive and significant effect on holistic satisfaction. Furthermore, Islamic service quality, spiritual care services, and holistic satisfaction significantly and positively influence patient loyalty. Holistic satisfaction partially mediates the relationship between Islamic service quality, spiritual care services, and patient loyalty. These results highlight the importance of integrating Islamic values and spiritual dimensions into healthcare services to enhance patient satisfaction and loyalty in Islamic hospitals.